2006
DOI: 10.1021/np060121y
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor CCR-5 Inhibitors Produced byChaetomiumglobosum

Abstract: Two novel chemokine receptor CCR-5 inhibitors, Sch 210971 (1) and Sch 210972 (2), were isolated from the fungal fermentation broth of Chaetomium globosum by normal- and reversed-phase HPLC purifications. The structure determination of 1 and 2 was accomplished on the basis of UV, MS, and NMR spectral data analyses including COSY, NOESY, HMQC, and HMBC experiments. The structure and relative configuration of 2 were determined unequivocally by X-ray crystallographic analysis. The major component 2 demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Comparative analysis of NMR and MASS revealed that compound ‘A’ is similar to Antibiotic Sch 210971 (m/z 445 and λ max 290) (Figure 8), which has previously been isolated from C. globosum by Yang et al (2006). In the finding by Yang et al molecular weight of the isolated compound was 445 Da and showed the protonated molecular ion at m/z + 446 similar to the compound isolated by us.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Comparative analysis of NMR and MASS revealed that compound ‘A’ is similar to Antibiotic Sch 210971 (m/z 445 and λ max 290) (Figure 8), which has previously been isolated from C. globosum by Yang et al (2006). In the finding by Yang et al molecular weight of the isolated compound was 445 Da and showed the protonated molecular ion at m/z + 446 similar to the compound isolated by us.…”
Section: Resultsmentioning
confidence: 68%
“…methanol and ethyl acetate were more active than hexane extract against S. sclerotiorum . Antibiotic Sch 210971 has been previously reported as chemokine receptor CCR-5 inhibitor (Yang et al 2006); however this is the first report of antifungal activity of this compound. HPLC has been utilized for the first time in our study in finding out the principle component of C. globosum responsible for antifungal activity.…”
Section: Discussionmentioning
confidence: 86%
“…This compound exhibits unique inhibitory activity against CCR-5, a cell surface receptor that allows the entry of HIV-1 into cells, and is an attractive lead compound for novel anti-HIV therapeutics. [8] Previous studies have shown that the tetramic acid moieties in related compounds, such as equisetin 2 [9] (Scheme 1) and cyclopiazonic acid [10] , are formed via a Dieckmann-type condensation that is catalyzed by reductive domains located at the C-termini of polyketide synthase nonribosomal peptide synthetase hybrid megaenzymes (PKS–NRPSs) [11] . Thus, we hypothesized that the framework of 1 was also biosynthesized by a hybrid PKS–NRPS.…”
mentioning
confidence: 99%
“…Yang and coworkers in 2006 screened secondary metabolites from the microbial extracts of fungi, actinomycetes, or bacteria [106]. A high-throughput screening utilizing a radioactive CCR5-binding assay that inhibited RANTES binding was conducted on the extracts and led to the discovery of two tetramic acids Sch210971 ( 45 , Figure 6) and Sch210972 ( 46 , Figure 6) with an IC 50 of 1.2 μM and 79 nM, respectively.…”
Section: Second-generation Small-molecule Ccr5 Antagonistsmentioning
confidence: 99%